RESEARCH ON THE ANTI-IMPACT CHARACTERISTIC AT DIFFERENT LOCATION BETWEEN THE MOVING SHIP AND MONOPILE OFFSHORE WIND TURBINES - ZHOU HongJie; LI Chun; HAO WenXing; YU Wan (Jixie qiangdu)
With tidal fluctuations, deep ship and deep draft changes, will inevitably lead to ship and offshore wind turbine collision location changes. In order to study the effect of collision location on the impact resistance of offshore wind turbine structure, a model of 3 MW wind turbine based on a monopile is established. The explicit dynamic theory and non-linear finite element method are used to simulate the 5 000 t impact of the wind turbine at different locations of the dynamic response process, through the support structure of the stress and crash depth, tower top response analysis of wind turbine structure crash performance. The results show that the higher the contact time is, the higher the contact force is. The higher the contact force is, the higher the contact force is, the higher the contact force is, the higher the contact force is. The lower the collision location of the support structure deformation energy and impact depth is greater than the collision location of the higher position. When the ship speed is 1 m/s, the higher the collision position, the greater the displacement and acceleration response of the tower wind turbine, When the ship speed is 4 m/s, the response amplitude of the tower wind turbine decreases as the collision position increases.